Epistemological Dissonance in Islamic Family Fiqh and Digital Ethics among Vocational High School Students - Zuhairiah; Ahmad Rizky (Al-Mudarris, 2026)
This study addresses a critical research gap in Islamic Religious Education (IRE), focusing on the epistemological disconnect between normative Fiqh knowledge and practical digital ethics among vocational students. While digital literacy is frequently examined as a technical or civic skill, its ontological and ethical foundation within Islamic family jurisprudence (fiqh al-usrah) remains under-explored. Utilizing a qualitative case study approach, data were gathered through in-depth interviews and digital behavior observations. The findings reveal a significant "internalization gap": although students demonstrate a high cognitive grasp of Family Fiqh, they experience severe dissonance when actualizing core values such as rahmah (compassion), ‘adl (justice), and mas’uliyyah (responsibility) within virtual spaces. This study identifies that the absence of a value-based pedagogical framework drives this lack of digital adab. As its primary theoretical contribution, this research proposes a “Maqasid-based Digital Ethics” model, transforming classical principles derived from Q.S. Ar-Rum (30): 21 into operational indicators for online conduct. This framework provides a vital pedagogical strategy for IRE teachers to bridge the gap between doctrinal religious education and contemporary digital social practices.